1946
DOI: 10.1002/pol.1946.120010408
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐catalyzed copolymerization of 1,3‐butadiene and styrene

Abstract: Butadiene and styrene have been copolymerized by the use of sodium sand as a catalyst. The copolymers containing 75 parts of butadiene and 25 parts of styrene and made at 30° and 50° are soluble in benzene and have intrinsic viscosities ranging from 2.5 to 7.5. The copolymers has a very nearly constant composition throughout the course of the polymerization. The amount of butadiene which has entered the chain by 1,2 addition is greater than in the case of the emulsion copolymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1947
1947
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Evidences of differences in molecular structure have been reported (5) and undoubtedly result from different mechanisms of polymerization. The work reported here was carried out to determine the suitability of sodium-catalyzed butadiene-styrene copolymers as general-purpose synthetic rubbers, and to provide a background for studies relating structure of elastomeric materials to their physical behavior.…”
Section: Sodium-catalyzedmentioning
confidence: 99%
“…Evidences of differences in molecular structure have been reported (5) and undoubtedly result from different mechanisms of polymerization. The work reported here was carried out to determine the suitability of sodium-catalyzed butadiene-styrene copolymers as general-purpose synthetic rubbers, and to provide a background for studies relating structure of elastomeric materials to their physical behavior.…”
Section: Sodium-catalyzedmentioning
confidence: 99%
“…Na-SG(II) and Na-SG(I) have found employment as drying agents to dry monomers and solvents (alone or mixed in a solution) for the anionic living polymerization of styrene and isoprene, despite the known ability of sodium sand to polymerize buta-1,3-diene and styrene. 34 The drying agent does not need to be removed before the polymerization step, as it does not interfere with the initiator. 35 At variance with this finding, it was also reported that the polymerization of methyl methacrylate can be initiated by Na-SG(I), but not by the second stage material.…”
Section: -O 2 Nc 6 H 4 Chmentioning
confidence: 99%
“…However, Coca Cola bottles which have been capped with a hand-capping machine are very convenient. The use of heavvwall screw-cap bottles has also been found satisfactory (7). Most of these applications have been to butadiene copolymer systems which were polymerized at low temperatures and correspondingly low pressures.…”
Section: Emulsion Polymerizationmentioning
confidence: 99%
“…Most of these applications have been to butadiene copolymer systems which were polymerized at low temperatures and correspondingly low pressures. The capped bottles often leak, but where the heat dissipation is poor, the pressure may rise rapidly and serious explosions have been reported (7). The polymerizations are conveniently carried out in a constant temperature cabinet or liquid bath.…”
Section: Emulsion Polymerizationmentioning
confidence: 99%